The Kafkaesque and the Absurd – Fear and Hope in the Writings of Franz Kafka and Albert Camus - Straehler-Pohl, Lars (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2022)
The world remains silent on the existential questions of human life. This existential silence is the defining moment both in the philosophy of Albert Camus and in the literary work of Franz Kafka. Silence manifests itself in the absurd as well as in the Kafkaesque, but those two perspectives differ in their implications with respect to hope. Kafka’s main protagonists in his three big novels are marked by the fluctuation between hope and fear. The uncertainty of their fate contrasts with the relative stability of Camus’s figures within his philosophy of the absurd. In contrast to prior research, the mythical figure of Sisyphus is here prominently considered. Sisyphus is without hope, whereas Josef K. (The Trial) is bound to it as to fear itself. The comparison of the two figures deviates from the classical analyses of Politzer (1960), Darzins (1960), Gillon (1961) and Bryant (1969), but also from newer approaches such as Viqez Jimenez (2017). Although the topic of hope has been analysed in some of these works, the article stresses the importance of hope in a terminological triplet. It examines hope, fear and silence in a philosophical perspective as a general approach to the Absurd and the Kafkaesque.